Multiple scattering of slow ions in a free electron gas - Archubi, Claudio Darío (2005)
We study the influence of electronic scattering on the angular distributions of ions and atoms moving through a free-electron gas. We present a general formulation based on the multiple-scattering formalism, using two alternative descriptions: a linear approach based on Lindhard’s dielectric function, and a nonlinear treatment based on density functional calculations. We obtain analytical expressions for the multiple-scattering function and for the half-width of the distribution. We show the results of several calculations for slow hydrogen and helium and their isotopes. We analyze the results and obtain analytical approximations for all of the cases. The magnitude of the electronic effects on the multiple scattering distribution is determined and compared with previous estimations.